EFFECTS OF BREADFRUIT LEAF ETHANOL EXTRACT ON IN VIVO LOWERING BLOOD GLUCOSE LEVELS - Herlina Herlina; Annisa Amriani; Dina Permata Wijaya; Filla Nur Oktriliansih (Fakultas MIPA Universitas Garut, 2022)
Breadfruit plant is traditionally used as a medicine for diabetes mellitus. Research has been conducted on the effects of ethanol extract of breadfruit leaves (Artocarpus altilis) against a decrease in the blood glucose levels of diabetic rats induced by allocation at a dose of 130 mg/kg bb. Breadfruit leaf ethanol extract (BLEE) is given orally at doses of 50, 100, and 200 mg/kg BW for 20 days. The test was conducted by measuring the blood glucose levels of rats with the GOD-PAP method. The observed parameters are blood glucose levels, ED 5,0 and pancreatic histopathology. The results showed a percentage decrease in blood glucose levels of 38,785%, 39,918%, and 44,925% of BLEE with successive doses of 50, 100, and 200 mg/kg BB that had significantly differences between groups (p<0.05). From the data obtained it can be concluded that BLEE 200 mg/kg BW has a decreased activity of blood glucose levels in which the pancreatic histopathology shows the improvement of endocrine cells islets of Langerhans almost perfect. Based on the percentage relationship of decreased blood glucose levels to dose, the effective dose (ED50) of BLEE is 329,341 mg/kg BW.